2018
DOI: 10.3390/ijms19030652
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Signaling Pathways and miRNAs by Resveratrol in Different Cancers

Abstract: Genomic and proteomic studies have helped improve our understanding of the underlying mechanism(s) of cancer development and progression. Mutations, overexpressed oncogenes, inactivated/downregulated tumor suppressors, loss of apoptosis, and dysregulated signal transduction cascades are some of the well-studied areas of research. Resveratrol has gained considerable attention in the last two decades because of its pleiotropic anticancer activities. In this review, we have summarized the regulation of WNT, SHH (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 72 publications
1
39
0
Order By: Relevance
“…Previous studies have shown that resveratrol has several anti‐inflammatory effects . In the CIA model, we found that resveratrol inhibited Src tyrosine kinase, STAT3, and Wnt signaling pathways, resveratrol‐ameliorated inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies have shown that resveratrol has several anti‐inflammatory effects . In the CIA model, we found that resveratrol inhibited Src tyrosine kinase, STAT3, and Wnt signaling pathways, resveratrol‐ameliorated inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 54%
“…Limagne et al have reported that resveratrol inhibits the IL‐6 and IL‐1β induced STAT3 activation in the cell culture of macrophages. It is known that resveratrol increases negative regulators of STAT signaling [SH2 domain‐containing tyrosine phosphatase (SHP‐2), protein inhibitor of activated STAT (PIAS), and protein tyrosine phosphatases (PTP)], and thus, it inhibits the activation of STAT . In our study, resveratrol decreased the mRNA expression of STAT3.…”
Section: Discussionmentioning
confidence: 61%
“…Accordingly, resveratrol‐treated SIRT1 null mice develop tumors at normal rates . In addition, there is a large body of evidence demonstrating that resveratrol suppresses the expression of various oncogenic miRNAs and upregulates tumor‐suppressor miRNAs in various cancer models …”
Section: Natural Compounds Possessing Epigenetic Properties That Stimmentioning
confidence: 99%
“…14 In addition, there is a large body of evidence demonstrating that resveratrol suppresses the expression of various oncogenic miRNAs and upregulates tumor-suppressor miRNAs in various cancer models. 75,83 The antitumor immunomodulatory properties of resveratrol have been highlighted in several studies and encompass the inhibition of immunosuppressive mechanisms in the TME and immune-enhancing properties. Resveratrol reportedly diminished Treg counts and functions ex vivo and in vivo, which are associated with the downregulation of TGF-β secretion from the spleen of EG7 lymphoma cell-induced and CT26 colon carcinoma cell-induced, tumor-bearing mice.…”
Section: Curcuminmentioning
confidence: 99%
“…The Special Issue included seven review papers that describe the current status of phenolic compounds, covering general aspects of their bioactivity for the suppression of chronic diseases [ 1 ], as well as the bioactivity of specific group of phenolics such as the stilbenoids [ 22 , 23 ], ellagitannins, and anthocyanins [ 24 ]. In addition, the health-promoting properties of phenolics present in lentils [ 25 ] and dry common beans [ 26 ] were also reviewed.…”
mentioning
confidence: 99%